From Expert to Elite? — Research on Top Archer’s EEG Network Topology - Gu, Feng; Gong, Anmin; Qu, Yi; Bao, Aiyong; Wu, Jin; Jiang, Changhao; Fu, Yunfa (Frontiers in Human Neuroscience, 2022)
It’s hard to be a sports expert, and even harder to grow from a sports expert to a sports elite. What is the difference between an expert and an elite, and how to grow from an expert to an elite, has always been a matter of great concern to professional athletes In order to explore the differences of brain neural mechanism between experts and elites in the process of motor behavior and reveal the internal connection between motor performance and brain activity, We collected and analyzed the electroencephalograph (EEG) of 14 national archers and 14 provincial archers during aiming and resting state, and constructed the EEG brain network of two groups of participants based on weighted phase lag index, the graph theory is used to analyze and compare the network characteristics from two aspects of local network topology and global network topology. The results showed that, compared with expert archer, elite archer had stronger functional coupling in beta1 and beta2 bands, and the difference was most obvious in frontal and central regions; the topological characteristics of global and local brain networks of elite archer were significantly stronger than that of expert archer; the brain network characteristics of expert archers showed a stronger correlation with archery performance. This reflects that elite archers show stronger functional coupling, higher integration efficiency of global and local information, and more independent performance in the archery process. These findings reveal the difference of brain electrical network topology between elite and expert archer in the preparation stage of shooting, and provide theoretical reference for further training, promotion and selection of professional athletes.